ASSA13-06-5 Autosomal Recessive Tansmission of MYBPC3 Mutation Resulted in Malignant Phenotpye of Hypertrophic Cardiomyopathy. (29th April 2013) - Yilu, Wang; Zhimin, Wang; Qi, Yang; Yubao, Zou; Hongju, Zhang; Chaowu, Yan; Xinxing, Feng; Yi, Chen; Yin, Zhang; Jizheng, Wang; Xianliang, Zhou; Ferhaan, Ahmad; et al.
Abstract : Background: Hypertrophic cardiomyopathy (HCM) secondary to mutations in genes encoding sarcomere proteins is most commonly inherited as an autosomal dominant trait. Since nearly 50% of HCM cases occur in the absence of a family history, a recessive inheritance pattern may be involved. Methods: A pedigree was identified with suspected autosomal recessive transmission of HCM. The proband and his younger brother were diagnosed with HCM, and his older brother incurred sudden cardiac death at 23 years of age. However, other family members were all clinically normal. Twenty-six HCM-related genes were comprehensively screened for mutations in the proband with targeted second generation sequencing, and the identified mutation was confirmed with bi-directional Sanger sequencing in all family members. Results: A novel missense mutation (c.1469G > T, p.Gly490Val) in exon 17 of MYBPC3 was identified. Two siblings with HCM were homozygous for this mutation, whereas other family members were either heterozygous or wild type. Clinical evaluation showed that both homozygotes manifested a typical HCM presentation, but none of others, including 5 adult heterozygous mutation carriers up to 71 years of age, had any clinical evidence of HCM. Conclusions: These data suggest that the inheritance pattern of HCM may be more complex than previously thought. The absence of a family history of clinical HCM may be due to not only a de novo mutation, but also recessive mutations that failed to produce a clinical phenotype in heterozygous family members. Therefore, consideration of recessive mutations leading to HCM is essential for risk stratification and genetic counselling.